From Instant History to the Infinite Archive: Digital Archiving, Memory and the Practical Past at the Roy Rosenzweig Center for History and New Media - da Silveira, Pedro Telles (Historein, 2018)
The September 11 Digital Archive and Hurricane Memory Digital Bank, both developed by the Roy Rosenzweig Center for History and New Media (CHNM) of George Mason University, are among two of the best known and most successful digital archiving initiatives. Though relatively old by internet standards and no longer receiving new submissions, both present a new understanding of what an archive is and its role regarding memory in contemporary society. Digital archives represent a convergence of social time and computer time, thus speeding the production of memory until it is contemporary of the event itself. This stretches the historical event beyond its limits but also means that the archive is created along with the event – it is an instant archive, so to speak. This contribution ends with a discussion on data accumulation in relation to Hayden White's notion of the practical past.